Social investment law or tax reform? (2022)
Law 2155 of 2021, called Law of Social Investment and sanctioned by the President of the Republic on September 14 of that year, is the last tax reform of the four presented in his government. The first one was overturned by the Constitutional Court due to procedural defects; the second one, which replaced the previous one, did become law, and the third was withdrawn by the President due to the pressure caused by the national strike. The different taxreform proposals of the Duque administration have had flashy names, perhaps to try to neutralize social rejection, but, even if he wants to sweeten their content and repercussions, they are basically tax reforms and that is how they should be named.